Choke point [compact disc, unabridged] - Pearson, Ridley (Brilliance Audio, 2013)
When an award-winning foreign journalist reveals the existence of an Amsterdam-based sweatshop known as a 'knot shop' that employs and enslaves young girls as laborers, private security firm Rutherford Risk is hired by a philanthropist to find it and shut it down.